2004
DOI: 10.1111/j.0022-2720.2004.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal orientation mapping of NiO grown on cube textured Ni tapes

Abstract: SummarySamples of cube textured Ni tapes were oxidized in flowing oxygen at different temperatures. Crystal orientation maps (COMs) of the resulting oxide layers were produced by electron backscatter diffraction. The oxide layers were also analysed by X-ray diffraction (XRD), scanning electron microscopy and atomic force microscopy (AFM). The oxide grain size of a sample oxidized at 600 ° C was similar to that of the substrate and the oxide was highly textured, both indicating epitaxial growth. The orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It has been reported that in the oxidation of highly textured Ni tapes the crystallographic orientation of the NiO grains is closely correlated with that of the Ni grains underneath. 35 Therefore, the annealing process prior to the NW growth helps to produce highly textured Ni foils and warrants the crystalline alignment of the produced NiO NW arrays. Furthermore, the NiO scale with fine channels limits the reaction rate and helps to protect the Ni foil from being etched excessively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in the oxidation of highly textured Ni tapes the crystallographic orientation of the NiO grains is closely correlated with that of the Ni grains underneath. 35 Therefore, the annealing process prior to the NW growth helps to produce highly textured Ni foils and warrants the crystalline alignment of the produced NiO NW arrays. Furthermore, the NiO scale with fine channels limits the reaction rate and helps to protect the Ni foil from being etched excessively.…”
Section: Resultsmentioning
confidence: 99%
“…During this process, the electric field of more than 10 6 V cm −1 developed between Ni and NiO, along with the giant mechanical stress at the interface, may assist the self-organized formation of the NiO NW arrays. It has been reported that in the oxidation of highly textured Ni tapes the crystallographic orientation of the NiO grains is closely correlated with that of the Ni grains underneath . Therefore, the annealing process prior to the NW growth helps to produce highly textured Ni foils and warrants the crystalline alignment of the produced NiO NW arrays.…”
Section: Resultsmentioning
confidence: 99%
“…[9]. The two observed fringe directions may be attributed to the difference in surface orientation or surface roughness of the corresponding substrates [18,19]. The direction in which a crystal grows on a substrate is dependent on the orientation of the seed crystal.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the (100) surfaces were the most readily oxidized at high temperature. 35,36 The reason nanocrystal growth governed by the VS process usually yields nanostructures with faceted shapes that consist of certain low index crystallographic planes is not clear in the present study. However, this method has some unique features compared with other existing physical approaches for growing nanocrystals of oxides or non-oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 72%